The new way to report correlations - Monge-Nájera, Julián (Universidad de Costa Rica, 2023)
Scientific communication is a crucial aspect of research that allows scientists to share their findings with the broader scientific community and the public. However, many scientific papers are difficult to understand because of the way they report statistical correlations. As a rule, the way you learned to do it, is not the best. Here I present a better, and valid, way to report correlations, with biological examples. Basically: state what they mean, rather than the raw result; and delete all obvious statements.